Peran Guru Ppkn Profesional Dalam Literasi Digital Dalam Pembelajaran Ppkn Di SMAN Nasrani 2 Medan Kelas X - Agustin Pratama Sihotang; Deo Agung Haganta Barus; Eirene Dahlia Sidabutar; Friska Lorentina Purba; Nasywa Yasmin Purba; Jamaludin Jamaludin (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Rapid technological advances are affecting various fields, one of which is education. Education cannot be separated from the progress that occurs. As an innovator, teaching in schools should be carried out by following all existing changes. In fact, students' digital literacy abilities are known to be in the low category so that each individual's learning needs are not achieved optimally. The aim of this research is to analyze how utilizing rapidly developing information and communication technology can help students meet their learning needs. Digital literacy is a form of ability to obtain, understand and use information originating from various sources in digital form. Literacy itself in the educational context plays a role in developing a person's knowledge of certain subject matter as well as encouraging curiosity and developing their creativity. This is what requires students to have literacy or the ability to process and understand good information to study and understand. With the rapid development of technology, it allows students to access information more easily. Digital literacy is also very necessary to overcome the problem of the ever-increasing explosion of information in digital sources. Society is now faced with very rapid technological developments. People are also required to sort and select information that is appropriate to the actual situation. Exposure to various kinds of information from the media makes most people doubt whether information is true or not. So with this phenomenon, media literacy knowledge is really needed as the ability to process information. This research method uses interviews with PPKn teachers in the city of Medan. The interview was conducted to see the extent of efforts made by PPKn teachers in increasing students' digital literacy. The result is that good digital literacy skills can enrich oneself with knowledge by actualizing oneself in these technological advances. The role of teachers in this case certainly cannot be replaced, but teachers can guide the extent to which students can utilize technology on the positive side and the extent to which they can minimize the possibility of deviating from the use of this technology.